Local heritage food as a significant factor in Malaysia gastronomy tourism / Hafizan Mat Som, Nani Masnida Nordin and Amzari Jihadi Ghazali. - Mat Som, Hafizan; Nordin, Nani Masnida; Ghazali, Amzari Jihadi (Universiti Teknologi Mara Selangor, 2019)
Food has been recognized as an effective promotional and positioning tool for a destination. Similarly, with the increasing interest in local cuisine, more destinations are focusing on food as their core tourism product. For example, France, Italy, and Thailand have been known for their cuisine. The importance of the connection between food and tourism cannot be ignored. Each destination has different levels of attractiveness that can draw tourists from different countries. Malaysia offers various kinds of food, including traditional and modern cuisines. As time goes by, the national heritage food is likely to be forgotten due to some factors such as lack of chefs and tourist awareness on this kind of food. Thus this research aims to investigate the level of awareness of food industry players on local heritage food, identifying the promotion effort implemented by the food industry players in marketing local heritage food and to explore the perception from food industry players on the potential, importance and opportunities of local heritage foods to be a factor of gastronomy tourism in Malaysia. The samples of a self-administered questionnaire were chefs who registered under the Malaysia Professional Chef Association (MPCA). It is shown that only one out of four hypotheses is statistically significant and has a strong relationship between the variables of the perception of the importance of local heritage food with the perception of the potential of local heritage food.